Perspectives of System Informatics: 11th International Andrei P. Ershov Informatics Conference, PSI 2017, Moscow, Russia, June 27-29, 2017, Revised Selected Papers - Petrenko, Alexander K; Voronkov, Andrei (Lecture Notes in Computer Science, 2018)
This book constitutes the refereed proceedings of the 11th International Andrei P. Ershov Informatics Conference, PSI 2017, held in Moscow, Russia, in June 2017.   The 31 full papers presented in this volume were carefully reviewed and selected from 57 submissions. The papers cover various topics related to the foundations of program and system development and analysis, programming methodology and software engineering and information technologies.